Dissection of Highly Prevalent qnrS1-Carrying IncX Plasmid Types in Commensal Escherichia coli from German Food and Livestock - Katharina Juraschek; Annemarie Käsbohrer; Burkhard Malorny; Stefan Schwarz; Diana Meemken; Jens André Hammerl (MDPI AG, 2021)
Plasmids are mobile genetic elements, contributing to the spread of resistance determinants by horizontal gene transfer. Plasmid-mediated quinolone resistances (PMQRs) are important determinants able to decrease the antimicrobial susceptibility of bacteria against fluoroquinolones and quinolones. The PMQR gene qnrS1, especially, is broadly present in the livestock and food sector. Thus, it is of interest to understand the characteristics of plasmids able to carry and disseminate this determinant and therewith contribute to the resistance development against this class of high-priority, critically important antimicrobials. Therefore, we investigated all commensal Escherichia (E.) coli isolates, with reduced susceptibility to quinolones, recovered during the annual zoonosis monitoring 2017 in the pork and beef production chain in Germany (n = 2799). Through short-read whole-genome sequencing and bioinformatics analysis, the composition of the plasmids and factors involved in their occurrence were determined. We analysed the presence and structures of predominant plasmids carrying the PMQR qnrS1. This gene was most frequently located on IncX plasmids. Although the E. coli harbouring these IncX plasmids were highly diverse in their sequence types as well as their phenotypic resistance profiles, the IncX plasmids-carrying the qnrS1 gene were rather conserved. Thus, we only detected three distinct IncX plasmids carrying qnrS1 in the investigated isolates. The IncX plasmids were assigned either to IncX1 or to IncX3. All qnrS1-carrying IncX plasmids further harboured a β-lactamase gene (bla). In addition, all investigated IncX plasmids were transmissible. Overall, we found highly heterogenic E. coli harbouring conserved IncX plasmids as vehicles for the most prevalent qnr gene qnrS1. These IncX plasmids may play an important role in the dissemination of those two resistance determinants and their presence, transfer and co-selection properties require a deeper understanding for a thorough risk assessment.